A study of tidal turbine array - Yong, Heng Wei. (2013)
In this globalisation world, there are ever-changing technologies happening around us all the times. When there are additional inventions and advancing technologies get into the world market, there will surely be an increasing demand of energy to run those equipments or gadgets. Due to the increase of greenhouse gases such as carbon dioxide, primarily produced by the burning of natural resources such as oil and coal. Natural disasters and human activities are the main reasons that contribute to an increase in average global temperatures, resulting global warming around the world. Alternate renewable resources are explored for immediate effect, hence the development of renewable energy such as wind, water and biofuel technologies are moving fast.